2012
DOI: 10.1111/j.1753-9137.2012.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Food and Agriculture: Stakeholder's Frames

Abstract: Despite its importance, the notion of sustainability is open for discursive struggle. This article's primary objective is to acquire insight into the manner in which the principal stakeholders strategically use frames in their public communication about sustainable food and agriculture. A framing analysis of 272 communications revealed a repertory of six culturally embedded frames: the value of responsibility, the metaphor of the undermining‐of‐foundations, the story of Frankenstein, the myth that all that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…This is consistent with Ingram's () findings in relation to soil management in England, where farmers were found to use a combination of both ‘scientific’ and ‘tacit’ knowledge. Van Gorp and van der Goot () add to this ‘mingling’ characterisation, by asserting that constructivist notions mooted in a sustainable agriculture context can be as mythical as objectivist notions and are limited: not all that comes from nature is axiomatically good.…”
Section: Objectivism and Constructivism In Knowledge For Sustainable mentioning
confidence: 99%
“…This is consistent with Ingram's () findings in relation to soil management in England, where farmers were found to use a combination of both ‘scientific’ and ‘tacit’ knowledge. Van Gorp and van der Goot () add to this ‘mingling’ characterisation, by asserting that constructivist notions mooted in a sustainable agriculture context can be as mythical as objectivist notions and are limited: not all that comes from nature is axiomatically good.…”
Section: Objectivism and Constructivism In Knowledge For Sustainable mentioning
confidence: 99%
“…Based on van Gorp and van der Goot [ 35 ], the Good Mother and Natural Goodness frames were expected to be found most frequently in video images and narratives. The third most used frame was Undermining of Foundations in both video groups.…”
Section: Resultsmentioning
confidence: 99%
“…Food-related framing usually falls into the corporative-political category [ 33 ] or into the social activism category [ 34 ]. Nonetheless, this study employed van Gorp and van der Goot [ 35 ] framing categories, which are used by stakeholders of sustainable food products and are based on archetypes ( Table 1 ). The “Natural Goodness” frame and the “Good Mother” frame are used frequently and are strongly interlinked [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With age, the low level of organic farming practice especially within the group younger than 30 and between 30-40 raises concern on the sustainability of the UK's agriculture. Gorp and Goot (2012) identified the importance of the younger generation in promoting and having a positive attitude towards sustainable agriculture. Even though these results are not positive for the future of UK's agriculture, the relationship between age and organic farming is expected, since an earlier study showed that the probability of adopting organic practice increases by 0.03 per cent for every year increase in age (Tiffin and Balcombe 2011).…”
Section: Implication Of Findings On Sustainable Agriculture In the Ukmentioning
confidence: 99%